A generalizable one health framework for the control of zoonotic diseases - Ria R. Ghai; Ryan M. Wallace; James C. Kile; Trevor R. Shoemaker; Antonio R. Vieira; Maria E. Negron; Sean V. Shadomy; Julie R. Sinclair; Grace W. Goryoka; Stephanie J. Salyer; Casey Barton Behravesh (Scientific Reports, 2022)
Abstract Effectively preventing and controlling zoonotic diseases requires a One Health approach that involves collaboration across sectors responsible for human health, animal health (both domestic and wildlife), and the environment, as well as other partners. Here we describe the Generalizable One Health Framework (GOHF), a five-step framework that provides structure for using a One Health approach in zoonotic disease programs being implemented at the local, sub-national, national, regional, or international level. Part of the framework is a toolkit that compiles existing resources and presents them following a stepwise schematic, allowing users to identify relevant resources as they are required. Coupled with recommendations for implementing a One Health approach for zoonotic disease prevention and control in technical domains including laboratory, surveillance, preparedness and response, this framework can mobilize One Health and thereby enhance and guide capacity building to combat zoonotic disease threats at the human–animal–environment interface.